Sufism in the Poems of Ahmad Kamal Abdullah: (Sufisme dalam Sajak Ahmad Kamal Abdullah) (Malay Literature, 2021)
This study aims to find sufi values in the poems of Ahmad Kamal Abdullah (Kemala), a modern Malaysian poet. In this study, the writer uses sufi literary theory to analyse poems by Kemala. The poems are taken from three collections of Kemala's poems, namely Ziarah Tanah Kudup (2006), Syurga ke Sembilan (2009), and Dhikr Serenades; Titir Zikir (2010). This study of sufi elements is the poems of Kemala employs the theory of Seyyed Hossein Nasr and concerns three major elements of tasawwuf (sufi mysticism), that is, the Divine, Mankind and spiritual wellbeing. The conclusion that can be drawn from this study is that the poems of Kemala are inseparable from sufism. The Divine is, in Kemala's poems, an aim in mankind's life journey. The Divine in this case is personified as light or "Nur". Mankind, in Kemala's poems, is depicted as the Salik or traveller in search of an end to his journey, which is the Divine Himself. While spiritual wellbeing is about the search and contemplation of human life.Keywords: Ahmad Kamal Abdullah, sufism, poem, sufi, tasawwuf